Separator for battery, battery, and method for manufacturing separator

By introducing negatively charged polymer nanoparticles into the porous glass fiber substrate separator, the problem of insufficient functionalization of the separator in alkali metal batteries is solved, and uniform deposition, inhibit dendrites' growth and enhance cycling performance are achieved.

CN119522506APending Publication Date: 2025-02-25INL INT IBERIAN NANOTECHNOLOGY LAB
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380048547.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-30
Filing Date
2023-06-28
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The functionalization of the separator in the existing alkali metal batteries is insufficient, especially in sodium metal batteries, and it is difficult to effectively inhibit dendrites' growth and achieve a stable solid-electrolyte interface.

Method used

Porous glass fiber substrate is used as the separator and negatively charged polymer nanoparticles are distributed on its surface. The particle concentration is increased over the entire thickness of the separator through a gravity-assisted migration step, thereby enhancing mechanical strength and ion conduction capabilities.

Benefits of technology

The uniform alkali metal deposition in alkali metal batteries is achieved, dendrite growth is inhibited, cycle performance and delayed capacity attenuation is enhanced, and challenges in actual battery applications are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119522506A_ABST
    Figure CN119522506A_ABST
Patent Text Reader

Abstract

The present invention relates to a separator for a battery comprising a porous glass fiber substrate having a first major surface and an opposing second major surface, and particles of a negatively charged polymer wherein the particles are distributed in the porous glass fiber substrate, such that the concentration of the particles increases over the entire thickness of the porous glass fiber substrate from the first major surface to the second major surface thereof. The invention also relates to a battery comprising said separator and to a method for producing said separator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a separator for a battery. In addition, the present invention relates to a battery comprising an anode, a cathode, an electrolyte and the separator, and a method for producing the separator. Background Art

[0002] Alkali metal batteries (AMBs) have attracted considerable research interest in recent years, as alkali metal (i.e., Li, Na, K) anodes offer much higher storage capacity than conventional anode materials (e.g., graphite for Li-ion batteries, hard carbon for Na-ion batteries). In addition, alkali metal batteries show significant potential for fast charging, since in this case, alkali metal plating replaces the kinetically limited alkali ion intercalation process, and thus high rate performance can be achieved. However, for the large-scale practical implementation of AMBs as energy storage devices with high energy density, mitigating dendrite formation / growth and achieving a stable solid-electrolyte interface (SEI) remain major challenges to overcome. To address these challenges, a variety of strategies have been developed, such as the use of three-dimensional (3D) current collectors, the introduction of artificial protective SEI on the surface of alkali metal anodes, and the optimization of the electrolytes used. To date, a lot of efforts have been made to directly modify alkali metal anodes and electrolyte engineering to suppress dendrite growth, thereby achieving long-term operation. However, to date, the functionalization of separators has received only minimal attention, especially for sodium metal batteries (SMBs).

[0003] Similar to electrode materials and electrolytes, separators are one of the most important components in AMBs. The separator not only physically and electrically isolates the anode and cathode to prevent short circuits, but also absorbs (uptake) electrolytes and serves as ion transport channels. It has recently been demonstrated that functionalizing the separator with ceramic materials or polymers can enhance its mechanical strength and thus inhibit lithium dendrite growth. However, these strategies cannot reduce the formation of dendrites to the desired level. In addition, surface-modified separators have been proposed to promote uniform Li deposition and regulate ion migration. However, these existing inorganic modifiers are generally brittle. In addition, it is very challenging to maintain the integrity of the inorganic layer of the modified separator and avoid delamination during battery cell manufacturing. This problem is even more prominent when manufacturing cylindrical or pouch-shaped battery cells that require a winding process.

[0004] Therefore, there is a need for improved battery components, such as improved separators.

[0005] Document WO2019 / 195605 discloses a method for making a highly stable metal anode (e.g., aluminum ion) battery. In some embodiments, the battery includes a composite separator for an ionic liquid electrolyte.

[0006] The document ZhangBo et al., Nano Energy, 10 (2014) discloses a composite membrane of glass microfibers and polyimide prepared by a papermaking method and a subsequent dip-coating method to explore the feasibility as a high-performance separator for lithium-ion batteries (LIBs).

[0007] Document EP1355366 discloses a separator in a lead-acid battery, which is composed of a fiber material and a polymer; the polymer provides the functions of increasing the mechanical strength of the separator, avoiding short circuits between the positive and negative electrodes, and reducing the thickness of the separator. The present invention also provides a method for manufacturing a battery separator, whereby a polymer is coated or adsorbed on a porous separator by spraying, dipping, brushing, adhering, etc., thereby obtaining a thinner battery separator with higher mechanical strength.

[0008] The above documents do not disclose a method including a gravity-assisted migration step to ensure a concentration gradient. Summary of the invention

[0009] In view of the above, it is an object of the present invention to provide an improved separator, an improved battery and an improved production method which together alleviate the above-mentioned disadvantages.

[0010] Another object is to provide a separator designed for use in batteries which has enhanced mechanical strength.

[0011] Another object is to provide a separator designed for batteries that regulates the plating and stripping of alkali metals to and from the anode and that reduces the formation and thus inhibits the growth of dendrites.

[0012] Another object is to provide a separator designed for a battery that enables a stable solid-electrolyte interface (SEI).

[0013] Another object is to provide a separator designed for use in batteries that promotes uniform alkali metal deposition and regulates ion transport.

[0014] Another object is to provide a separator designed for batteries with enhanced cycling performance and delayed capacity fade.

[0015] Another object is to provide a separator designed for batteries that overcomes the challenges of practical application of AMBs as energy storage devices with high energy density.

[0016] Another object of the present invention is to provide a separator that can be used in various battery cells. Separators are used in a variety of batteries to electrically separate the anode from the cathode, prevent short circuits, and at the same time provide an ion conduction path that allows alkali metal ions to move back and forth between the anode and the cathode.

[0017] Another object is to provide a separator that not only physically and electrically isolates the anode and cathode to prevent short circuits, but also absorbs electrolyte and serves as an ion transport channel.

[0018] Another object is to provide a separator designed for use in batteries that is easy and inexpensive to manufacture.

[0019] In order to achieve at least one of the above objects and other objects that will be clear from the following description, according to the present invention, there is provided a separator having the features defined in claim 1. According to claim 11, there is provided a battery comprising the separator, and according to claim 13, there is provided a method for manufacturing the separator. The dependent claims will make preferred variations of the inventive concept clear.

[0020] According to a first aspect, there is provided a separator for a battery, comprising: a porous glass fiber substrate having a first major surface and an opposite second major surface, and particles of a negatively charged polymer, wherein the particles are distributed in the porous glass fiber substrate such that a concentration of the particles increases throughout the thickness of the porous glass fiber substrate from the first major surface to the second major surface thereof.

[0021] The term "porous fiberglass substrate" refers to a general nonwoven material comprising glass fibers randomly arranged crosswise with each other. However, the fiberglass substrate can be composed of a woven material embedded with glass fibers. However, the nonwoven fiberglass substrate is generally a material with greater mechanical strength than the woven fiberglass substrate, because its randomly arranged fibers constitute the main skeleton. Porous materials generally refer to materials including pores, cavities or void spaces. Therefore, the fiberglass substrate contains void spaces or pores, i.e., spaces not occupied by the main skeleton of the fibers constituting the fiberglass substrate structure. The properties and structure of the pores of the fiberglass substrate depend on the manufacturing parameters and the materials used for the substrate. For example, the pore size and thickness of the porous fiberglass substrate can be customized by selecting the starting material and the manufacturing process. The porous fiberglass substrate is generally moldable, so it can be manufactured in different forms, such as balls, plates, rods, fibers, ultra-thin films, tubes and rings. The porous fiberglass substrate can be a commercially available fiberglass substrate.

[0022] The term "major surface" means that the substrate has two major surfaces that are opposite to each other such that the substrate extends between the two surfaces, more in one direction other than in the direction between the two surfaces, typically forming the shape of a sheet.

[0023] The term "particle" refers to a small part, component, body or element of a substance. Here, the particle usually has micrometer and / or nanometer size. Therefore, the term "microparticle" is a particle of micrometer size, i.e. greater than 1000 nm and at most 1000 μm, and "nanoparticle" is a particle of nanometer size, i.e. greater than 1000 pm and at most 1000 nm. The particles of the present invention can be uniform in size or mixed in size ranging from nanometer size to micrometer size. Preferably, the particles have nanometer size.

[0024] The role of nanoparticles or nanospheres in the separator is that they can help redistribute the ion flow and promote uniform deposition of alkali metal ions such as Li+, Na+ or K+ without hindering ion transport. The redistribution is usually achieved through the interstices of the filled nanoparticles and the local electric field induced by the negatively charged polymer.

[0025] "Negatively charged polymer" refers to the presence of negative charges on the surface of the polymer. Whether the polymer is negatively or positively charged may depend on the solution pH and may be measured by the zero charge point method. The zero charge point (pzc) is the pH at which the net surface charge of the polymer is equal to zero. pzc can usually be obtained by acid-base titration. According to the present invention, due to the locally enhanced electric field, the negatively charged polymer helps to accelerate the transfer of alkali metal cations. In order to achieve the acceleration effect, at least the main part of the polymer is preferably "negatively charged". Unlike small molecules, polymers have ultra-high molecular weights, resulting in possible heterogeneity of the polymer. As far as "negatively charged" is concerned, it can be attributed to the effect of the "polymer main group", which can attract some "positive particles" due to its super strong negative effect. In the case of the present invention, alkali metal ions, such as Li+ or Na+, can be "attracted" near the polymer surface, redistributing the Li+ or Na+ flow, which can help to improve the uniform deposition of these metal ions.

[0026] The advantage of negatively charged polymer nanoparticles is that they will enhance the local electric field strength, promoting the transfer of alkali metal ions to the anode when the battery is charged.

[0027] The increase in nanoparticle concentration in the porous glass fiber can be a "wave increase", that is, an increase with an ups and downs from the first major surface to the second major surface throughout the thickness of the porous glass fiber substrate, so that the concentration of nanoparticles is lowest at the first major surface and highest at the second major surface.

[0028] The separator of the present inventive concept achieves several significant advantages.

[0029] The separator conceived by the present invention has the advantage that, in addition to separating the anode from the cathode and thus preventing short circuits, it also serves as an ion transport channel. However, by impregnating negatively charged polymer particles into the glass fiber separator, it has the additional function of being able to homogenize the alkali metal deposition when charging in an alkali metal battery, assuming that the filled nanoparticles redistribute the ion flow and enhance the local electric field, thereby promoting the transfer of alkali metal ions. In particular, the glass fiber separator embedded with PTFE is ion-permeable. The presence of the PTFE-nanoparticles is to regulate the ion flux.

[0030] Therefore, another advantage of the inventive concept of introducing negatively charged polymer nanoparticles into glass fiber separators is to homogenize alkali metal plating, i.e., to obtain uniform deposition of alkali metal on the anode during charging, thereby inhibiting dendrite growth and thus eliminating related battery failures.

[0031] Another advantage of the present invention is that it aims to solve the problems of using alkali metals (including lithium, sodium or potassium) as anodes in alkali metal batteries, mainly dendrite growth, thereby improving energy density.

[0032] The particle concentration in the porous glass fiber substrate can increase throughout the thickness of the porous glass fiber substrate from the first major surface to the second major surface, such that the particle concentration is lowest at the first major surface and highest at the second major surface.

[0033] The meaning of "continuously increasing" can be considered as "gradually increasing", which is not necessarily "uniform", but the particle concentration in the porous glass fiber substrate still increases toward the second major surface. This is advantageous because it is better in controlling the ion flux.

[0034] The term "at the surface" means that the particles are embedded within the glass fiber matrix at a small distance from the surface. Thus, the particles are not coated or layered on the surface of the glass fiber matrix, but rather reside in the glass fiber matrix immediately adjacent to the surface.

[0035] The thickness of the porous glass fiber substrate may be in the range of 10 - 150 μm, preferably 50 μm.

[0036] The thickness of the glass fiber substrate is important. The thinner the better, as this will reduce the ionic impedance during charge / discharge. However, the glass fiber substrate of the separator cannot be too thin. If a too thin glass fiber substrate is used in the separator, a short circuit may occur. The glass fiber substrate can be of any shape and size. The separator can be customized to the size associated with the battery in which the separator is used.

[0037] The porous glass fiber substrate may have an average pore size of 0.1 - 10 μm, preferably 0.3 - 2 μm, preferably about 0.5 μm.

[0038] The term "pore size" refers to the average extension of the openings or holes in the material. The pore size of the porous glass fiber substrate given by the supplier is usually nominal. In practice, for example, under scanning electron microscope (SEM) observation, the pore size is usually larger than the nominal pore size. However, the pore size can be smaller than the nominal pore size. The maximum pore size is preferably in the range of 2-3 microns. If the pore size is too large, it may cause a short circuit when the separator is used in a battery.

[0039] The particles may have an average extension in the range of 30 nm - 2 μm, preferably 100 - 300 nm, preferably about 210 nm.

[0040] The term "extends" refers to the average distance of the long diameter of the particle. The particles can have different shapes, which can be defined by the relative sizes of the long axis, the middle axis and the short axis of the particle. The ratio of the median diameter to the long diameter and the ratio of the short diameter to the median diameter can be used to define four shape categories, which can be selected from: flat, such as a sheet or disk form; long, such as a rod; blade-like; and isodiametric, such as a cube or a sphere. Preferably, the particle is a nanosphere.

[0041] The separator may also have a second major surface having a 5 – 10 9 The areal number density of particles can be in the range of 100 particles / mm2 of separator. The areal number density of particles such as nanoparticles can be closely related to the average particle size. For nanoparticles with an average size of 210 nm, the areal number density of particles can be optimally in the range of 0.5×10 7 – 4×10 7 However, if nanoparticles with a smaller size, such as 100 nm, are used, the surface number density needs to be increased accordingly to achieve similar results. The nanoparticles or nanospheres are usually filled or provided three-dimensionally in the glass fiber separator.

[0042] 20-95% of the volume of the separator may be occupied by particles, preferably 55-80% of the volume of the separator may be occupied by particles. Thus, the separator may have a "filling degree" as a volume % of the total volume of the separator.

[0043] The polymer of the negatively charged particles may be selected from the group consisting of fluorine-containing polymers, chlorine-containing polymers, carboxylic acid-containing polymers, sulfonate-containing polymers, amide bond-based polymers, and polyester-based polymers, as well as salts, derivatives, and complexes thereof.

[0044] The term "composite" means that there may be a "blend" or "mixture" of a "negatively charged polymer" and some other material, including an inorganic filler or some other polymer or the like.

[0045] The fluoropolymer may be selected from the group consisting of polytetrafluoroethylene (PTFE), fluorinated ethylene propylene copolymer (FEP) and polyvinylidene fluoride (PVDF).

[0046] The term "fluoropolymer" or "fluorinated polymer" is interpreted as a fluorocarbon-based polymer having multiple carbon-fluorine bonds. Thus, a fluoropolymer is a fluorine-containing polymer that primarily includes a polymer of repeating monomer units or monomers based on a number of fluoroalkyl substances. A fluoropolymer can be a homopolymer of one monomer unit or a copolymer of two or more monomers. For example, polytetrafluoroethylene (PTFE) is a typical fluoropolymer. The structure of formula I shows the structure of PTFE, where the monomer units are in brackets and n represents the number of repeating units, where n can tend to infinity, preferably n is at least 100. The average molecular weight of a fluoropolymer can be in the range of 1.4×10 4 to 1.2×10 6 g / mol range.

[0047]

[0048] Formula I

[0049] The fluoropolymer may be polytetrafluoroethylene, which has the advantage that polytetrafluoroethylene consists only of carbon and fluorine, which makes PTFE hydrophobic and water-repellent. Therefore, neither water nor water-containing substances wet PTFE.

[0050] Another example of a fluoropolymer is fluorinated ethylene propylene copolymer (FEP), which is a copolymer of hexafluoropropylene and tetrafluoroethylene. It differs from polytetrafluoroethylene (PTFE) resin in that it is melt processable using conventional injection molding and screw extrusion techniques. FEP is very similar to PTFE in composition and has the useful properties of low friction and non-reactivity of PTFE, but is easier to shape. Another example of a fluoropolymer is polyvinylidene fluoride (PVDF), which is a highly non-reactive thermoplastic fluoropolymer prepared by polymerization of vinylidene fluoride.

[0051] The chlorine-containing polymer may be represented by polyvinyl chloride (PVC).

[0052] The carboxylic acid-containing polymer may be represented by poly(methacrylic acid).

[0053] The sulfonate-containing polymer may be selected from the group consisting of sodium polystyrene sulfonate and polyethylene sulfonic acid.

[0054] The polymer based on the amide bond group can be selected from: polyamides, such as polyamide 6.6, i.e. nylon, polyamide 6, polyamide 6.10, polyamide 11, etc., and polyacrylamide (PAM). Polyamide is a polymer having repeating units connected by amide bonds. It has a linear structure. Polyacrylamide (PAM) is a polyolefin having the formula (-CH2CHCONH2-). Therefore, it can be regarded as a polyethylene with amide substituents on alternating carbons. Unlike various nylons, PAM is not a polyamide because the amide group is not in the polymer backbone. PAM is highly hygroscopic and forms a soft gel when hydrated. Therefore, the polymer based on the amide bond can be a polymer connected by amide bonds or a polymer modified by amide bond groups.

[0055] Polyester-based polymers can be represented by polyhydroxyalkanoates (PHA). PHA is a polyester produced by various microorganisms in nature. PHA can be a thermoplastic or elastomeric material with a melting point ranging from 40-180°C. The advantage of PHA is that their mechanical properties can be changed by blending, modifying the surface or combining PHA with other polymers or inorganic materials, so they can have a wide range of applications. In addition, PHA can be biodegradable and biocompatible.

[0056] Preferably, the polymer of the negatively charged particles may be polytetrafluoroethylene. The advantage of PTFE is that it provides a strong separator that provides improved uniformity of alkali metal deposition when charging in an alkali metal battery. It also provides enhanced control of the flux of alkali metal ions.

[0057] The polymer of the negatively charged particles may be polytetrafluoroethylene, and the particle surface number density at the second major surface may be 0.5×10 7 – 4×10 7 The surface number density of PTFE particles can be as high as 1.6×10 7 particles / mm2. The particles may have an average extension of 210 nm.

[0058] According to a second aspect, there is provided a battery, comprising:

[0059] An anode, a cathode, an electrolyte, and a separator according to the first aspect of the invention, wherein the separator is arranged between the anode and the cathode, wherein the electrolyte occupies the void space of the separator, and wherein the first major surface of the separator faces the cathode, and the second major surface of the separator faces the anode.

[0060] Here, a "battery" may be a primary battery or a secondary battery, i.e., a non-rechargeable or rechargeable battery, preferably, the battery is rechargeable. A battery according to the present invention may include at least one electrochemical unit cell, in which a single anode and cathode are separated by an electrolyte for generating voltage and current. A battery according to the present invention may include a plurality of electrochemical units.

[0061] In general, the features of this aspect of the invention provide similar advantages as discussed above with respect to the previous aspects of the invention. Therefore, in order to avoid excessive repetition, the advantages will not be repeated. However, an advantage of the battery conceived by the present invention is that, considering the uniform distribution of the alkali metal ion flow, the dendrite growth has been suppressed in the first cycle of charging, which will be unlikely to cause dendrite formation and its subsequent growth in the cycle. Another advantage of the battery conceived by the present invention is to have enhanced cycle performance and delayed capacity decay.

[0062] The anode may include an element selected from the group consisting of Li, Na, and K, and combinations thereof.

[0063] The advantage of the anode of the present invention is that it provides a uniform solid electrolyte interface layer on the anode surface, protecting or passivating the alkali metal to prevent reaction with the electrolyte during electrochemical cycling. In addition to the advantage that the anode and separator together can inhibit dendrite growth on the anode, the anode can also achieve a stable electrolyte / electrode interface that is less prone to undesirable reactions.

[0064] The cathode can include a cathode material selected from the group consisting of a Li intercalation compound, a Na intercalation compound, or a potassium intercalation compound.

[0065] The term "intercalation compounds" refers to cathode materials that allow reversible insertion and extraction of Li+, Na+ and K+. These are the most commonly used types of cathode materials in secondary Li / Na / K batteries today. Examples of cathode materials can be LiNiO2, LiCoO2, LiNi x Co y Mn z O2 (x+y+z = 1), LiNi a Co b Mg c Al d O2 (a+b+c+d = 1), LiMnO2,LiNi 0.5 Mn 0.5 O2, Li2MnO3, xLi2MnO3·(1-x)LiMO2 (M = Ni, Co, Cr), LiMn2O4, LiNi x Mn yO4(x+y = 2), LiFePO4, LiMnPO4, LiCoPO4, LiNiPO4, Li2FeSiO4, Li2MnSiO4, NaFePO4,Na (1-x) K x PO4, KFePO4, Na 0.7 FePO4, Na 1.5 VOPO4F 0.5 , Na3V2(PO4)3, Na3V2(PO4)2F3,Na2FePO4F, NaFeF3, NaVPO4F, KVPO4F, Na3V2(PO4)2F3, Na 1.5 VOPO4F 0.5 , Na3V2(PO4)3,NaV6O 15 , Na x VO2, Na 0.33 V2O5, Na x CoO2, Na 2 / 3 [Ni 1 / 3 Mn 2 / 3 ]O2, Na x [Fe 1 / 2 Mn 1 / 2 ]O2, Na x MnO2,λ-MnO2, Na x K (1-x) MnO2, Na 0.44 MnO2, Na4Mn9O 18 , NaFe2Mn(PO4)3, Na2Ti3O7, Ni 1 / 3 Mn 1 / 3 Co 1 / 3O2, Cu 0.56 Ni 0.44 HCF, NiHCF, NaCrO2, KCrO2, Na3Ti2(PO4)3, NiCo2O4, NaFe(CN)6 / C, KFe(CN)6 / C, NaV 1-x Cr x PO4F, Prussian blue, Prussian white and combinations thereof. Preferably, the cathode material may include LiFePO4 (LFP) or Na3V2(PO4)3F3 (NVP).

[0066] In another embodiment of this aspect, the cathode may comprise sulfur, selenium or oxygen / air. Sulfur as a cathode material acts differently from an intercalation compound. Alkali metal cations will form compounds with sulfur during discharge, such as Li / Na / KS, Li / Na / K-Se or Li / Na / K-O2, which then decompose during charging. Therefore, the battery chemistry is different from using an alkali metal intercalation compound as a cathode material.

[0067] With respect to the present disclosure, an "electrolyte" or "electrolyte layer" has properties that provide ions and ion mobility sufficient for the composition to be used as an electrolyte in an electrochemical cell. The electrolyte can be, for example, selected from lithium hexafluorophosphate, LiPF6 in ethylene carbonate / diethyl carbonate (LiPF6 / EC / DEC), LiPF6 / ethylene carbonate / dimethyl carbonate (LiPF6 / EC / DMC), bis(trifluoromethanesulfonyl)-imide / 1,2-dimethoxyethane / 1,3-dioxolane lithium (LiTFSi / DME / DOL), sodium hexafluorophosphate (NaPF6) in ethylene carbonate / diethyl carbonate (NaPF6 / EC / DEC), sodium hypochlorite (NaClO4) in ethylene carbonate / diethyl carbonate (NaClO4 / EC / DEC), or sodium bis(trifluoromethanesulfonate)imide (NaTFSI) in polyethylene oxide (NaTFSI / PEO). For example, 1 M LiPF6 or 1 M NaPF6 in a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) can be used as the electrolyte.

[0068] The inventive concept according to the second aspect can also be extended to other metal-air batteries, such as zinc-air batteries, in which metal plating and stripping are the main processes occurring at the anode during charging and discharging. Therefore, the battery according to the second aspect is not limited to alkali metal batteries.

[0069] According to a third aspect, there is provided a method for making a separator according to the first aspect of the invention, the method comprising: wetting a porous glass fiber substrate having a first major surface and an opposing second major surface with a dispersion of negatively charged polymer particles in a solvent,

[0070] While the particles migrate toward the second major surface of the porous glass fiber substrate under gravity-assisted migration, the solvent of the dispersion is evaporated from the porous glass fiber substrate such that the concentration of the particles increases throughout the thickness of the porous glass fiber substrate from the first major surface to the second major surface thereof.

[0071] The term "gravity-assisted migration" means that the particles will move towards a downwardly directed major surface, ie, by the downward pull of gravity.

[0072] Wetting can include drop casting or spraying the dispersion onto the porous glass fiber substrate, or immersing the porous glass fiber substrate in the dispersion. For example, spraying can be pressure-based, through a nozzle or by electrospraying.

[0073] The evaporation may further comprise heating the porous glass fiber substrate at a temperature of 50-200° C., preferably 90° C., for a period of 2-24 hours, preferably 10 hours. The heating temperature depends on the polymer used. The heating temperature should be below the melting temperature of the polymer so that it does not melt during the evaporation of the solvent.

[0074] Generally, the features of this aspect of the invention provide similar advantages as discussed above with respect to the previous aspects of the invention. Therefore, in order to avoid excessive repetition, the advantages will not be repeated.

[0075] However, the advantage is that the method is an operationally simple and cost-effective permeation and evaporation method with less cost and readily available commercial materials.

[0076] The use of the separator according to the first aspect of the invention in a battery according to the second aspect of the invention may advantageously be provided.

[0077] Other features and advantages of the present invention will become apparent when studying the attached claims and the following description. Those skilled in the art will recognize that different features of the present invention may be combined to produce variations other than those described below, however the present invention is defined by the attached claims. Features of one aspect may be related to any of the other aspects. BRIEF DESCRIPTION OF THE DRAWINGS

[0078] The above and other aspects of the inventive concept will now be described in more detail with reference to the accompanying drawings showing variations of the inventive concept. The accompanying drawings should not be considered as limiting the inventive concept, rather they are used to explain and understand the inventive concept.

[0079] As shown in the drawings, the sizes of layers and regions are exaggerated for illustrative purposes and are thus provided to illustrate the general structures of variations of the inventive concepts.

[0080] Figure 1 A schematic diagram of a method for manufacturing a separator is shown.

[0081] Figure 2 A schematic diagram of a battery including an anode, a cathode, a separator, and an electrolyte filled in the separator is shown.

[0082] Figure 3 A block diagram of a method for producing the separator is schematically shown.

[0083] Figure 4A low magnification cross-sectional SEM image of a PTFE-glass fiber separator is shown.

[0084] Figure 5 A high magnification cross-sectional SEM image of a PTFE-glass fiber separator is shown.

[0085] Figure 6 SEM images showing Li deposition in a half-cell with a PTFE-glass fiber separator are shown.

[0086] Figure 7 Shown are SEM images showing Na deposition in a half-unit cell with a PTFE-glass fiber separator.

[0087] Figure 8 SEM images showing Li deposition in a half-cell with a bare glass fiber separator are shown.

[0088] Fig. 9 Shown are SEM images showing Na deposition in a half-cell with a bare glass fiber separator.

[0089] Fig.10 Shown is the XPS spectrum of the Cu current collector after Li deposition.

[0090] Fig.11 Shown is the XPS spectrum of the Cu current collector after Na deposition.

[0091] Fig.12 Schematically shown is the distribution of the current density vector between the anode and cathode in the presence of a PTFE-nanoparticle layer without application of an external voltage.

[0092] Fig.13 Schematically shown is the distribution of the current density vector between the anode and the cathode in the presence of two layers of PTFE nanoparticles without application of an external voltage.

[0093] Fig.14 Schematically shown is the distribution of the current density vector between the anode and the cathode in the presence of three layers of PTFE-nanoparticles without application of an external voltage.

[0094] Fig.15 Schematically shown is the distribution of the current density vector between the anode and cathode in the presence of a PTFE nanoparticle layer when an external voltage of 0.2 V is applied.

[0095] Fig.16 Schematically shown is the distribution of the current density vector between the anode and cathode in the presence of two PTFE-nanoparticle layers when an external voltage of 0.2 V is applied.

[0096] Fig.17 Schematically shown is the distribution of the current density vector between the anode and cathode in the presence of three PTFE-nanoparticle layers when an external voltage of 0.2 V is applied.

[0097] Fig.18 Schematically shown is the anode thickness variation in the presence of three PTFE-nanoparticles during Li plating when an external voltage of 0.2 V is applied.

[0098] Fig.19 Schematically shown is the anode thickness variation in the presence of five PTFE-nanoparticles during Li plating when an external voltage of 0.2 V is applied.

[0099] Fig. 20 Schematically shown is the anode thickness variation in the presence of thirteen PTFE-nanoparticles during Li plating when an external voltage of 0.2 V is applied.

[0100] Fig.21 shows that at 0.5 mA cm -2 Electrochemical performance in terms of cycling stability of PTFE-glass fiber separators in Li / / Li symmetric unit cells measured under .

[0101] Fig. 22 The results show that the Na / / Na symmetric unit cell has a high -2 Electrochemical performance in the form of cycling stability of the PTFE-glass fiber separator measured under .

[0102] Fig.23 Shown is the electrochemical performance in terms of cycling stability of the PTFE-glass fiber separator in Li / / LFP full cell measured at 1C rate.

[0103] Fig.24 Shown is the electrochemical performance in terms of cycling stability of PTFE glass fiber separator in Na / / LVP full cell measured at 1C rate. DETAILED DESCRIPTION

[0104] The inventive concept will now be described more fully below with reference to the accompanying drawings, in which preferred variations of the inventive concept are shown. However, the inventive concept can be implemented in many different forms and should not be construed as being limited to the variations set forth herein; on the contrary, these variations are provided for thoroughness and completeness and fully convey the scope of the invention to the skilled person. Although individual features may be included in different variations, these features may be combined in other ways, and inclusion in different variations does not mean that a combination of features is not feasible. In addition, references to the singular do not exclude the plural. In the context of the present invention, the terms "one", "an" do not exclude multiple (individuals).

[0105] The present invention discloses a novel separator 1 , a battery 10 including the separator 1 , and a method 100 for manufacturing the novel separator 1 .

[0106] The separator 1 described herein may be defined as a protective layer between the anode 20 and cathode 30 in the battery 10 by preventing short circuits but enabling the electrolyte 40 to absorb and act as a channel for ion transport.

[0107] like Figure 1 As schematically shown in FIG. 1 , separator 1 is generally produced by method 100 (also in Figure 3 ), the method comprising wetting 101, for example by drop-casting or spraying a dispersion onto the porous glass fiber substrate 2, or immersing the porous glass fiber substrate 2 in a dispersion of particles of a negatively charged polymer 5 in a solvent, such as a suspension of PTFE. During solvent evaporation 102, the suspension tends to move downward from the first major surface 3 under gravity-assisted migration, so that the concentration of particles 5 increases over the entire thickness of the porous glass fiber substrate 2 from its first major surface 3 to its second major surface 4, for example resulting in a high-density condensation of PTFE-nanoparticles on the second major surface 4 of the separator 1. The evaporation 102 may also comprise heating 103 the porous glass fiber substrate 2 at a temperature of 50-200° C., preferably 90° C., and for a period of 2-24 hours, preferably 10 hours, such as Figure 3 shown.

[0108] X-ray diffraction (XRD) examination of the PTFE-glass fiber separator 1 manufactured according to the above shows a sharp peak at 18.0° and several weak peaks at 31.5°, 36.6°, 37.1° and 41.3°, which can be attributed to PTFE. In contrast, the bare glass fiber separator 2 has a featureless XRD pattern, indicating the amorphous structure of the glass fiber. The Fourier transform infrared (FT-IR) transmission spectrum of the PTFE-glass fiber separator 1 manufactured according to the above reveals that the peaks at 501.4, 553.5, 638.3, 1151.3 and 1207.2 cm -1There are several valleys at the bottom, which correspond to -CF2-rocking, -CF2-wagging, -CF2-bending, -CF2-symmetric stretching and -CF2-asymmetric stretching modes, respectively. Therefore, it is confirmed that the PTFE-nanoparticles 5 are successfully incorporated into the separator 1. In addition, the concentration of the particles 5 in the porous glass fiber substrate 2 can continuously increase from the first major surface 3 to the second major surface 4 throughout the thickness of the porous glass fiber substrate 2, so that the concentration of the particles 5 is the lowest at the first major surface 3 and the highest at the second major surface 4. The porous glass fiber substrate 2 can have a thickness in the range of 10-150μm, or preferably a thickness of about 50μm. Scanning electron microscopy (SEM) was further performed to examine and confirm the cross-sectional morphology of the glass fiber substrate 1. Compared with the original or bare glass fiber separator, the PTFE-glass fiber separator 1 shows obvious contrast in its cross section (see Figure 4 ), indicating that the PTFE-nanoparticles are concentrated on one side of the separator, namely the second major surface 4. A careful observation clearly reveals the spherical nature of the PTFE and that these nanospheres are densely packed (see Figure 5 ).

[0109] The porous glass fiber substrate 2 may have an average pore size of 0.1-10 μm, preferably 0.3-2 μm, preferably about 0.5 μm. It is therefore suitable for capturing or retaining particles 5 having an average extension range of 30 nm-2 μm, preferably 100-300 nm, preferably about 210 nm. In addition, the filling degree may be that 20-95% of the volume of the separator 1, preferably 55-80% of the volume of the separator 1 is occupied by particles 5.

[0110] When the glass fiber has been impregnated or filled with particles of a negatively charged polymer 5, it may result in an area number density of particles 5 at the second major surface 4 of 10 5 – 10 9 The negatively charged polymer particles 5 may be selected from the group consisting of fluorine-containing polymers, chlorine-containing polymers, carboxylic acid-containing polymers, sulfonate-containing polymers, amide-based polymers, and polyester-based polymers, as well as their salts, derivatives, and complexes. Preferably, the negatively charged polymer of the particles 5 may be polytetrafluoroethylene, wherein the surface number density of the PTFE particles 5 at the second major surface 4 is typically 0.5×10 7 – 4×10 7 particles / mm2, preferably 1.6×10 7 particles / mm2, and wherein the PTFE particles have an average extension of 210 nm.

[0111] exist Figure 2, a battery 10 is shown, which includes: an anode 20, a cathode 30, an electrolyte 40, and a separator 1 that can be arranged between the anode 20 and the cathode 30, wherein the electrolyte 40 occupies the void space of the separator 1, and wherein the first major surface 3 of the separator 1 faces the cathode 30, and the second major surface 4 of the separator 1 faces the anode 20. The anode 20 may include an element selected from the following: Li, Na and K and combinations thereof.

[0112] Therefore, to further investigate how the introduction of PTFE-nanoparticles 5 into the separator 1 affects the electrodeposition of Li and Na during charging of the battery 10, a coin cell was assembled, which contained the separator 1 of the present invention (wherein the negatively charged polymer particles were PTFE-nanoparticles) and a bare glass fiber separator 2, which was sandwiched by the Li or Na metal disk and Cu foil current collector of the half-cell, respectively.

[0113] The term "half-cell" refers to an alkali metal anode paired with a copper (Cu) foil current collector separated by a separator 1 according to the present invention, which is mainly used to study the coulombic efficiency of alkali metal plating and stripping when the battery is charged and discharged.

[0114] In addition, 1 M LiPF6 or 1 M NaPF6 in a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) was used as the electrolyte 30. For Li or Na metal plating, 0.5 mA cm -2 The current density is 2 hours. Figure 6 and Figure 7 As shown, in the presence of PTFE-nanoparticles 5 in the glass fiber separator 1, the Li and Na deposits on Cu in the Li and Na half-cells show a continuous, uniform and relatively smooth surface, respectively. In contrast, with the bare glass fiber separator, “mossy” deposits were observed in the Li half-cell (see Figure 8 ), a discontinuous island microstructure was found in the Na half-cell (see Fig. 9 ). However, when the surface chemistry of the deposits was analyzed using X-ray photoelectron spectroscopy (XPS), it was found that the Li and Na deposits exhibited Li-F and Na-F bonds on their surfaces (see Fig.10 and Fig.11 ). This means that the presence of PTFE-nanoparticles 5 in the glass fiber separator 1 makes the ion flow distribution during the plating process uniform, resulting in uniform and flat Li and Na metal films. In addition, the redistribution of ion flow can promote the formation of alkali metal fluorides, which helps ion conduction.

[0115] In order to gain insight into the uniform deposition of Li and Na metals in the presence of PTFE-nanoparticles 5 within the glass fiber separator 1, the distribution of alkali ion flux (reflected by the current density vector) and the local electric field were simulated using COMSOL Multiphysics using the tertiary current distribution and Nernst-Planck model. In the absence of PTFE-nanoparticles 5 and an external voltage between the anode 20 and the cathode 30, the current density vector and the electric field between the two electrodes exhibited an inhomogeneous spatial distribution, which became uniform when an external voltage of 0.2 V was applied. In order to simulate the effect of PTFE-nanoparticles 5, negatively charged point charges were introduced near the anode 20, assuming that PTFE is generally negatively charged and that the size of the nanoparticles may be quite small compared to the electrode surface and therefore can be considered as point charges. The introduction of PTFE-nanoparticles 5 changes the distribution of the current density vector and the electric field (see Fig.12 , 13 and 14), but the distribution is non-directional and disordered. Fig.12 , 13 14 show the distribution of the current density vector between the anode and cathode in the presence of one, two or three layers of PTFE-nanoparticles respectively without applying an external voltage. These different layers can be Fig.12 , 13 After applying an external voltage of 0.2 V, the current density vector becomes more directional and locally enhanced, and the electric field distribution becomes more uniform compared to the zero voltage condition (see Fig.15 , 16 and 17). Fig.15 shows the current density vector between the anode and cathode in the presence of a PTFE-nanoparticle layer, while Fig.16 and 17 The current density vector between the anode and cathode in the presence of two and three PTFE-nanoparticle layers is shown, respectively. This may be particularly prominent with the increase in the PTFE-nanoparticle layer. The enhanced local electric field can promote the rapid transport of Li+ and Na+ cations to the anode 20. This is experimentally confirmed by measuring the migration numbers of Li+ and Na+ cations. In the battery containing the PTFE-glass fiber separator 1, the migration numbers of Li+ and Na+ are 0.81 and 0.93, respectively, which are about 2 and 3 times the migration numbers obtained in the unit cell containing the bare glass fiber separator 2 (i.e., 0.41 for the Li unit cell and 0.32 for the Na unit cell). This clearly shows that, unlike the previously reported separators with inorganic materials textured on their surfaces to enhance mechanical robustness, the introduction of negatively charged polymer PTFE-nanoparticles 5 not only confers significantly improved flexibility in unit cell production, but also helps to accelerate the inherent Li+ and Na+ transport.

[0116] In order to further investigate the deposition of Li and Na metals across the PTFE-glass fiber separator 1 in detail, it was investigated how the spatial distribution of the PTFE-nanoparticles 5 affects the thickness variation of the metal deposits. To this end, 3, 5, and 13 negative point charges were introduced near the anode 20 of the Li cell, respectively, to simulate different packing densities of the PTFE-nanoparticles 5 in the glass fiber separator 1. A large thickness variation of 0.035 nm was observed in the presence of three PTFE-nanoparticles 5 (see Fig.18 ), which would produce a deposit with a large characteristic size. However, when the number of PTFE-nanoparticles is increased to 5 (see Fig.19 , variation: about 0.014nm) and 13 (see Fig. 20 , change: 0.002 nm), the change drops sharply. This will significantly reduce the characteristic size of the deposit, leading to a more uniform deposition of Li and Na metals, thereby suppressing dendrite formation. Simulations of the Na plating process produce similar results.

[0117] The role of PTFE-NPs in suppressing dendrite growth and extending the cycle life of Li and Na metal batteries 10 was further confirmed in Li / / Li and Na / / Na symmetric unit cell tests.

[0118] The "symmetric unit cell" consists of two identical alkali metal electrodes as working electrode and counter electrode, respectively, separated by a separator according to the present invention, which is mainly used to evaluate the long-term cycling performance of the electrodes.

[0119] The symmetric unit cell contains two symmetric Li or Na metal foils as anode 20 and cathode 30, respectively, which are separated by PTFE-glass fiber separator 1 or bare glass fiber separator 2. The Li / / Li unit cell with bare glass fiber separator 2 has a high conductivity at 0.5 mA cm -2 The polarization voltage is 0.018 V (capacity: 0.5 mAh cm -2 , Fig.21 The black trace in Figure 1). The polarization voltage suddenly dropped to 0.005 V after 718 h and then changed irregularly, indicating that a short circuit occurred somewhere in the cell due to Li dendrite growth during continuous cycling. In complete contrast, the Li / / Li cell containing PTFE glass fiber separator 1 showed stable polarization under the same conditions for up to 1245 h without signs of short circuit ( Fig.21 ). At 0.5 mA cm -2The morphology of the Li metal electrode was examined after 200 cycles of plating under PTFE-nanoparticles 5. In the presence of PTFE-nanoparticles 5, the Li foil showed a relatively smooth surface morphology, while for the cell containing the bare glass fiber separator 2, dendritic Li appeared after 200 cycles of plating under the same conditions. The promoting effect of PTFE-nanoparticles on cyclability was more prominent in the Na / / Na symmetric cell (see Fig. 22 ), where the cell with PTFE glass fiber separator 1 can be reversibly charged and discharged for 1375 cycles (2750 h) with a fairly stable polarization voltage (about 0.08 V), showing much better performance than the cell with a bare glass fiber separator that failed after only 250 cycles (500 h). In addition, the surface of the Na metal electrode after cycling in the former cell appears much smoother than that in the latter cell, with no or almost no dendrites and rough structures observed.

[0120] Furthermore, the effectiveness of the PTFE nanoparticle impregnation on the cycling stability was also demonstrated in full cell tests. A "full cell" comprises an alkali metal anode 20, a corresponding cathode 30 and a separator 1 according to the invention in between. This represents the configuration of a real working battery cell 10.

[0121] In this case, commercial LiFePO4 (LFP) and homemade Na3V2(PO4)3F3 (NVP) according to embodiments of the present invention were used as active cathode materials in Li and Na cells, respectively. The Li / / LFP cells containing PTFE-glass fiber separator 1 and bare glass fiber separator 2 both showed capacity drop at the beginning of cycling at 1C rate (see Fig.23 ), which may be caused by the rapid consumption of electrolyte after Li dendrite growth. “1C” means that the battery can be fully charged / discharged in one hour. These are standard test conditions for evaluating cycling stability. However, for the PTFE-glass fiber separator 1 containing Li / / LFP unit cell, the capacity retention is greater than 70% of the initial value after about 290 cycles, while the Li / / LFP unit cell without PTFE-glass fiber separator shows rapid decay after 60 cycles and finally fails after 175 cycles. It is worth noting that by using PTFE-glass fiber separator 1, the capacity retention rate of Na / / NVP unit cell can reach 91% after 340 cycles (see Fig.24 ), which is significantly better than the unit cell containing only bare glass fiber separator 2.

[0122] Experimental details

[0123] Chemicals and Materials

[0124] Polytetrafluoroethylene dispersion (60 wt.% PTFE-nanoparticles in H2O), glass fiber separator (Whatman, CAT No. 1802-150), cetyltrimethylammonium (CTAB, ≥96%), sodium fluoride (NaF, >99.5%), vanadium oxide (V2O3, >99.7%), diammonium phosphate (NH4H2PO4, >98%), phosphoric acid (H3PO4, >85 wt.%), lithium disk, sodium ingot, and all other chemicals and solvents used to prepare the electrolyte, including LiPF6, NaPF6, ethylene carbonate (EC, anhydrous ≥99.0%), and diethyl carbonate (DEC, anhydrous ≥99.0%), were purchased from Sigma-Aldrich and used as received. LiFePO4 was purchased from Contemporary Amperex Technology Co, Limited (CATL).

[0125] Preparation of PTFE-glass fiber separator

[0126] The PTFE dispersion was used to prepare an undiluted PTFE-glass fiber separator 1. Typically, 60 μL of the PTFE dispersion was spread on the surface of a disk of a 10 mm diameter round glass fiber separator 2. After the dispersion was completely wetted into the separator, the sample was transferred to a ventilated fume hood and kept still for 12 hours. The PTFE-glass fiber separator 1 was then placed in a vacuum oven and heated at 120°C for 12 hours to completely remove moisture, and then placed in an Ar-filled glove box for use in button cell batteries.

[0127] Synthesis of Na3V2(PO4)3F3 (NVP) cathode material

[0128] According to previous reports, the NVP cathode material was synthesized following a modified procedure. Briefly, 3.645 g of CTAB was dissolved in a mixture of 120 mL of anhydrous ethanol and deionized water (12:1, v / v). After stirring for 2 h under N2 atmosphere, 0.63 g of NaF and 0.75 g of V2O3 were added to the mixed solution. After stirring for another 30 min, 1.725 g of NH4H2PO4 was poured into the aforementioned mixture, and the solution was continuously stirred for 24 h under N2 atmosphere. Subsequently, the resulting black precipitate was collected and dried at room temperature in a N2 flow. After grinding in a mortar, the dried solid product was placed in a tube furnace preheated at 120 °C and then calcined at 750 °C under argon atmosphere for 6 h. The heating rate was set to 5 °C min -1 and the furnace was cooled naturally to room temperature.

[0129] Material characterization

[0130] The morphologies of the PTFE-glass fiber separator, metallic Li and Na electrodes, and the prepared NVP powders were examined by scanning electron microscopy (SEM, FEI Quanta 650 FEG) and the Cu K α Their crystal structures were characterized by X-ray diffraction (XRD) on an X'Pert PRO diffractometer (PANalytical) set at 45 kV and 40 mA using 10-nanometer radiation (λ = 1.541874 Å) and a PIXcel detector. Fourier transform infrared (FT-IR) spectra were obtained using a VERTEX 80v vacuum FTIR spectrometer. The surface chemistry of the electrodes was characterized using an ESCALAB 250 Xi X-ray photoelectron spectrometer (XPS) with an Al source (1486.6 eV). The take-off angle between the electrode surface and the analyzer was 90°, and the images were taken at 650 × 400 μm. 2 Signals at the core levels of C1s, Li1s, Na1s and F1s were collected within the analysis area.

[0131] simulation

[0132] The simulations were performed using COMSOL Multiphysics software with an implemented finite element solver. The “Electrodeposition, three-level Nernst-Planck” model was used to simulate the local electric field distribution, and the “Deformed Geometry” module was used to simulate the inhomogeneous changes of the electrode boundaries during the deposition process. A point potential of −0.01 V was applied to simulate the effect of negatively charged PTFE-nanoparticles on the electric field distribution and Li / Na deposition. The initial concentration of alkali metal ions was set to 1000 mol m -3 , the exchange current density is limited to 100A m -2 The temperature was fixed at 293.15 K. The anodic and cathodic potentials were set to 0.1 and −0.1 V for Li and Na deposition, respectively.

[0133] Cell assembly and electrochemical testing

[0134] All electrochemical tests were performed using 2032 coin cells assembled in a glove box filled with 99.999% argon. For half-cell tests, a piece of Li or Na foil (10 mm diameter, 1 mm thickness) and a circular Cu foil with the same area were used as the working electrode and counter electrode, respectively, which were separated by a pristine glass fiber or PTFE-glass fiber separator (12 mm diameter). 1M LiPF6 in EC / DEC or 1M NaPF6 in EC / DEC were used as electrolytes for the Li or Na cell, respectively. Similar structures were also used for symmetric cells, but two symmetric Li or Na metal foils were used in these cases.

[0135] For the fuel cell tests, the cathode 30 was first prepared according to a previously reported procedure. Briefly, LFP or NVP active materials were mixed with Super P in the presence of n-methyl-pyrrolidone (NMP) in a powder mixer. ® The slurry was mixed with polyvinylidene fluoride (PVDF) binder in a weight ratio of 8:1:1 (for LFP) or 7:2:1 (for NVP). The resulting slurry was then doctor-casted on an aluminum current collector. The loading densities of the LFP and NVP active materials were approximately 1.25 and 2.55 mg cm, respectively. -2 The symmetric and full-cell Li and Na cells were subjected to galvanostatic charge / discharge tests using a WonATech battery test station (WBCS3000S1). Cyclic voltammetry (CV) of all cells was performed on a Biologic VMP3 electrochemical workstation. 1C corresponds to 150 mA g for Li / / LFP and Na / / NVP full-cell cells, respectively. -1 and 100 mA g -1 of charge / discharge current density.

Claims

1. A separator (1) for an alkali metal battery (10), comprising: a porous glass fiber substrate (2) having a first major surface (3) and an opposing second major surface (4), and particles of a negatively charged polymer (5), the negatively charged polymer being selected from the group consisting of fluorine-containing polymers, chlorine-containing polymers, carboxylic acid-containing polymers, sulfonate-containing polymers, amide bond-based polymers and polyester-based polymers, and salts, derivatives and complexes thereof, The particles (5) are distributed in the porous glass fiber substrate (2) such that the concentration of the particles (5) increases throughout the thickness of the porous glass fiber substrate (2) from the first major surface (3) to the second major surface (4).

2. The separator (1) according to claim 1, wherein the concentration of the particles (5) in the porous glass fiber substrate continuously increases from the first main surface (3) to the second main surface (4) throughout the thickness of the porous glass fiber substrate (2), so that the concentration of the particles (5) is lowest at the first main surface (3) and highest at the second main surface (4).

3. The separator (1) according to claim 1 or 2, wherein the porous glass fiber substrate (2) has a thickness of 10-150 μm.

4. The separator (1) according to any one of claims 1 to 3, wherein the porous glass fiber substrate (2) has an average pore size in the range of 0.1 - 10 μm.

5. The separator (1) according to any one of claims 1 to 4, wherein the particles (5) have an average extension in the range of 30 nm - 2 μm, preferably 100 - 300 nm.

6. The separator (1) according to any one of claims 1 to 5, wherein the surface number density of the particles (5) at the second main surface (4) is between 10 5 – 10 9 The separator (1) has a range of 100 particles / mm2.

7. The separator (1) according to any one of claims 1 to 6, wherein 20 - 95% of the volume of the separator is occupied by the particles (5).

8. The separator (1) according to any one of claims 1 to 8, wherein the polymer of the negatively charged particles (5) is polytetrafluoroethylene.

9. The separator (1) according to claim 9, wherein the surface number density of the particles at the second main surface is between 0.5×10 7 – 4×10 7 The particles are in the range of 210 nm / mm2 and wherein the particles have an average extension of 210 nm.

10. An alkali metal battery (10), comprising: an anode (20) comprising an element selected from the group consisting of Li, Na and K and combinations thereof, cathode (30), electrolyte (40), and The separator (1) according to any one of claims 1 to 10, wherein the separator (1) is arranged between the anode (20) and the cathode (30), wherein the electrolyte (40) occupies the void space of the separator (1), and The first major surface (3) of the separator (1) faces the cathode (30), and the second major surface (4) of the separator (1) faces the anode (20).

11. A method (100) for producing a separator according to any one of claims 1 to 10, the method comprising: Wetting (101) a porous glass fiber substrate (2) having a first major surface (3) and an opposing second major surface (4) with a dispersion of negatively charged polymer particles (5) in a solvent, While the particles (5) migrate toward the second major surface (4) of the porous glass fiber substrate (2) under gravity-assisted migration, the solvent of the dispersion is evaporated (102) from the porous glass fiber substrate (2) so that the concentration of the particles (5) increases throughout the thickness of the porous glass fiber substrate (2) from its first major surface (3) to its second major surface (4).

12. The method (100) according to claim 13, wherein the wetting (101) comprises drop-casting or spraying the dispersion onto the porous glass fiber substrate (2) or immersing the porous glass fiber substrate (2) in the dispersion.

13. The method (100) according to claim 13 or 14, wherein the evaporating (102) further comprises heating (103) the porous glass fiber substrate (2) at a temperature of 50-200°C for a period of 2-24 hours, preferably 10 hours.

Citation Information

Patent Citations

  • Separator in lead acid battery and manufacturing method therof

    EP1355366A2

  • Glass fiber composite separator

    WO2019195605A1